A facile and regioselective synthesis of 1-tetralones via silver-catalyzed ring expansion1. Issue 29 (7th August 2015) - Yu, Jiajia; Zhao, Huijun; Liang, Shuguang; Bao, Xiaoguang; Zhu, Chen
<x xml:space="preserve">Abstract</x> A regioselective synthesis of 1-tetralones via silver-catalyzed ring expansion is described.